Mechanism of NLRP3 inflammasome intervention for synovitis in knee osteoarthritis: A review of TCM intervention - Han, Xianfu; Lin, Demin; Huang, Weiwei; Li, Dingpeng; Li, Ning; Xie, Xingwen (Frontiers in Genetics, 2023)
Objective: This paper briefly reviews the structure and function of NLRP3 inflammasomes, signaling pathway, relationship with synovitis in KOA, and intervention of traditional Chinese medicine (TCM) in NLRP3 inflammasomes as a means to improve its therapeutic potential and clinical application. Method: Literatures about NLRP3 inflammasomes and synovitis in KOA were reviewed to analyze and discuss. Result: NLRP3 inflammasome can activate NF-κB mediated signal transduction, which in turn causes the expression of proinflammatory cytokines, initiates the innate immune response, and triggers synovitis in KOA. The TCM monomer/active ingredient, decoction, external ointment, and acupuncture regulating NLRP3 inflammasomes are helpful to alleviate synovitis in KOA. Conclusion: The NLRP3 inflammasome plays a significant role in the pathogenesis of synovitis in KOA, TCM intervention targeting the NLRP3 inflammasome can be a novel approach and therapeutic direction for the treatment of synovitis in KOA.